Hydrogenation catalyst as well as preparation method and application thereof
By using alumina-lanthanum oxide-titanium oxide composite support and N-graphyne in the hydrogenation catalyst, a high dispersion active phase is formed, which solves the problem of low activity of existing hydrogenation catalysts and achieves efficient hydrodesulfurization and denitrogenation Performance and simple preparation method, suitable for industrial petroleum refining.
Patent Information
- Application Number
- CN202310855021.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-14
AI Technical Summary
The existing hydrogenation catalysts have low hydrodesulfurization and denitrification activities, and are complex in preparation methods, making it difficult to operate on industrial equipment.
The aluminum oxide-lanthanum oxide-titanium oxide composite support and N-graphyne as the support and active components of the hydrogenation catalyst were prepared by impregnation method to form a highly dispersed active phase, inhibit high-temperature agglomeration phenomenon, and improve the hydrogenation activity of the catalyst. .
It significantly improves the hydrodesulfurization and denitrification activity of the hydrogenation catalyst, enhances the stability and life of the catalyst, simplifies the preparation process, and is suitable for industrial applications.
Smart Images

Figure CN119303597A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of petroleum refining, and in particular to a hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] At present, hydrodesulfurization is the main method to reduce the sulfur content in distillate oil raw materials. Hydrodesulfurization, hydrodenitrogenation, olefin saturation and other reactions can be carried out simultaneously to produce clean oil products or their blending components.
[0003] The National VI Standard for automotive gasoline and diesel requires that the sulfur content of hydrogenated products should not exceed 10 mg / kg. Therefore, hydrodesulfurization activity is the most critical indicator of hydrogenation catalysts. In addition, although the nitrogen content in inferior distillate oil is lower than the sulfur content, nitrides will have a huge impact on the stability of oil products. The presence of nitrides has a strong inhibitory effect on the removal of sulfides, especially alkaline nitrides are more easily adsorbed on the acidic center of the catalyst and are not easy to desorb, which directly leads to a decrease in the number of active centers of the catalyst, affecting the activity and life of the catalyst, causing the catalyst to be poisoned and deactivated, and ultimately affecting the quality of the hydrogenated product. Therefore, reducing the nitrides in the fraction is of great significance to improving the activity of the hydrodesulfurization reaction.
[0004] The catalyst prepared by using mesoporous magnesium oxide loaded with Co and Mo in CN103157518A has high catalytic activity for the hydrodesulfurization reaction of dibenzothiophene compounds. However, the stability of the magnesium oxide carrier is greatly different from that of the aluminum oxide carrier, the hydrogenation activity is not high, and the preparation route is complicated, making it difficult to operate on an industrial device.
[0005] In order to improve the activity of the catalyst, CN1052501A adds additives P, F, and B to the impregnation solution containing the three metals Co-W-Mo, adopts the segmented impregnation method, and obtains the finished catalyst after drying and roasting. After the active metal is impregnated, it is roasted at high temperature. The interaction between the active metal component and the carrier is strong, which affects the sulfurization effect of the catalyst, and also causes some active metal components to aggregate, affecting the dispersion of the active metal, and further affecting the activity of the catalyst.
[0006] The hydrogenation catalyst in CN102851061A uses Si-modified alumina and ETS-10 titanium silicon molecular sieve with a grain size of less than 2 μm as carriers, and Fe, Co, Ni, Mo, and W as active components. The catalyst can reduce the sulfur content of inferior gasoline to less than 50 μg / g, the nitrogen content to less than 50 μg / g, and the olefin content to less than 30 vol.%, and the octane number loss of the product is less than 3 units; when processing high-sulfur diesel, the sulfur content is reduced to less than 50 μg / g, the nitrogen content is reduced to less than 20 μg / g, and the diesel yield is greater than 99.8 wt.%. However, the microporous structure of the ETS-10 molecular sieve is not conducive to the reaction of large molecular sulfur and nitrogen compounds, and the hydrogenation activity needs to be improved.
[0007] In summary, there is an urgent need for a hydrogenation catalyst with high hydrodesulfurization activity and a simple preparation method. Summary of the invention
[0008] The purpose of the present invention is to overcome the problem of low desulfurization and denitrification activity of hydrogenation catalysts in the prior art and to provide a hydrogenation catalyst and a preparation method and application thereof.
[0009] In order to achieve the above object, the present invention provides a hydrogenation catalyst in a first aspect, wherein the hydrogenation catalyst comprises: a carrier, an active component and N-graphene; wherein the active component is supported on the carrier, and the N-graphene is supported on the carrier or mixed in the carrier;
[0010] Wherein, the carrier comprises an aluminum oxide-lanthanum oxide-titanium oxide composite carrier;
[0011] Wherein, the active component is selected from sulfides of at least two kinds of metals M;
[0012] wherein the metal M is selected from Group VIII and Group VIB;
[0013] Wherein, based on the total mass of the hydrogenation catalyst, the content of N-graphene in the hydrogenation catalyst is 0.1-5wt%.
[0014] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the preparation method comprises the following steps:
[0015] (1) treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, an extrusion aid and a binder to obtain a carrier;
[0016] (2) mixing an aqueous solution containing an active component precursor and N-graphene to obtain an impregnation solution, wherein the active component precursor is selected from compounds of at least two of the metals M;
[0017] (3) impregnating the support into an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor;
[0018] or:
[0019] A. treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, N-graphene, an extrusion aid and a binder to obtain a base material;
[0020] B. mixing aqueous solutions containing active component precursors to obtain an impregnation solution, wherein the active component precursors are selected from compounds of at least two of the metals M;
[0021] C. Immersing the base material in an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor;
[0022] wherein the metal M is selected from Group VIII and Group VIB;
[0023] The amount of N-graphene used is such that the content of N-graphene in the prepared hydrogenation catalyst is 0.1-5wt% based on the total amount of the hydrogenation catalyst;
[0024] Wherein, the preparation method further comprises sulfiding the hydrogenation catalyst precursor to obtain the hydrogenation catalyst.
[0025] The third aspect of the present invention provides a hydrogenation catalyst prepared by the above preparation method.
[0026] A fourth aspect of the present invention provides use of the above hydrogenation catalyst in petroleum refining.
[0027] Through the above technical scheme, the hydrogenation catalyst provided by the present invention and its preparation method and application can achieve the following beneficial effects:
[0028] (1) In the present invention, the hydrogenation catalyst uses an aluminum oxide-lanthanum oxide-titanium oxide composite carrier as a composite carrier, which weakens the interaction between the carrier and the active component and can further improve the hydrogenation activity of the hydrogenation catalyst.
[0029] (2) In the present invention, the introduction of N-graphene into the hydrogenation catalyst helps to form a highly dispersed active phase, inhibits agglomeration during high temperature, and then accurately regulates the structure of the hydrogenation active phase to form a highly dispersed type II phase hydrogenation active center, which significantly improves the hydrogenation activity of the catalyst. The hydrogenation catalyst has high hydrodesulfurization and denitrification activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is the BET diagram of the hydrogenation catalyst of Example 1;
[0031] Figure 2 This is a TEM image of the hydrogenation catalyst of Example 1. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] The first aspect of the present invention provides a hydrogenation catalyst, wherein the hydrogenation catalyst comprises: a carrier, an active component and N-graphene; wherein the active component is supported on the carrier, and the N-graphene is supported on the carrier or mixed in the carrier;
[0034] Wherein, the carrier comprises an aluminum oxide-lanthanum oxide-titanium oxide composite carrier;
[0035] Wherein, the active component is selected from sulfides of at least two kinds of metals M;
[0036] wherein the metal M is selected from Group VIII and Group VIB;
[0037] Wherein, based on the total mass of the hydrogenation catalyst, the content of N-graphene in the hydrogenation catalyst is 0.1-5wt%.
[0038] In the present invention, the hydrogenation catalyst uses an aluminum oxide-lanthanum oxide-titanium oxide composite carrier as a composite carrier, which weakens the interaction between the carrier and the active component, improves the dispersion of the active metal, and can further enhance the hydrogenation activity of the hydrogenation catalyst.
[0039] In the present invention, N-graphene can be used as a carrier or attachment site of active metals, and can physically isolate active sites and improve the dispersion of active phases. At the same time, N-graphene has a unique electronic structure, which can realize rapid electron transfer, facilitate hydrogen overflow, enhance the synergistic effect between active metal sites, and thus improve the catalyst activity.
[0040] In the present invention, N-graphene helps to form a highly dispersed active phase, inhibits agglomeration during high temperature, and then accurately regulates the structure of the hydrogenation active phase to form a highly dispersed type II phase hydrogenation active center, which significantly improves the hydrogenation activity of the catalyst. The hydrogenation catalyst has high hydrodesulfurization and denitrification activity.
[0041] According to the present invention, based on the total mass of the hydrogenation catalyst, the content of N-graphene in the hydrogenation catalyst is 0.5-3wt%.
[0042] In the present invention, when the content of N-graphene is 0.5-3wt%, the hydrodesulfurization and denitrification performance is more excellent.
[0043] In the present invention, the introduction of titanium oxide in the alumina-lanthanum oxide-titanium oxide composite carrier improves the hydrodesulfurization and denitrification performance of the hydrogenation catalyst. Specifically, titanium oxide has a variable valence state, which can adjust the surface properties of the carrier, change the distribution and chemical state of the active components, and enhance the hydrogen overflow activity.
[0044] According to the present invention, based on the total mass of the hydrogenation catalyst, the content of lanthanum oxide in the hydrogenation catalyst is 1-10wt%, the content of titanium oxide is 1-10wt%, the content of aluminum oxide is 40-77.9wt%, and the content of active components in terms of oxides is 20-35wt%.
[0045] According to the present invention, preferably, based on the total mass of the hydrogenation catalyst, the content of lanthanum oxide in the hydrogenation catalyst is 2-6wt%, the content of titanium oxide is 2-6wt%, the content of aluminum oxide is 55-70.5wt%, and the content of active components in terms of oxides is 25-30wt%.
[0046] In the present invention, when the contents of lanthanum oxide, titanium oxide, aluminum oxide and active components meet the above-mentioned limitations, the dispersion state of the hydrogenation catalyst is better and the catalytic performance is more excellent.
[0047] According to the present invention, at least two of the metals M are selected from at least two of Mo, W, Co and Ni, preferably Mo-Ni, W-Ni, Mo-Co, Mo-Ni-Co, W-Ni-Co or W-Mo-Ni-Co.
[0048] In the present invention, N-graphene and the alumina-lanthanum oxide-titanium oxide composite carrier can further improve the hydrodesulfurization and denitrification performance.
[0049] According to the present invention, the shape of the hydrogenation catalyst is flake, spherical, cylindrical, shaped, granular or toothed spherical.
[0050] According to the present invention, the special-shaped strip is in the shape of a three-leaf clover, a four-leaf clover or a butterfly.
[0051] According to the present invention, the diameter of the cylindrical strip or the special-shaped strip is 1.0-1.8 mm.
[0052] According to the present invention, the specific surface area of the hydrogenation catalyst is 200-300m 2 / g.
[0053] According to the present invention, the pore volume of the hydrogenation catalyst is 0.4-0.7 mL / g.
[0054] According to the present invention, the lateral pressure strength of the hydrogenation catalyst is 160-200 N / cm.
[0055] According to the present invention, the bulk density of the hydrogenation catalyst is 0.6-0.9 g / cm 3 .
[0056] In the present invention, the hydrogenation catalyst has specific components and contents, so that the hydrogenation catalyst has good lateral pressure strength and specific specific surface area, pore solvent and bulk density.
[0057] According to the present invention, the specific surface area of the hydrogenation catalyst is 230-260m 2 / g.
[0058] According to the present invention, the pore volume of the hydrogenation catalyst is 0.45-0.65 mL / g.
[0059] According to the present invention, the lateral pressure strength of the hydrogenation catalyst is 170-190 N / cm.
[0060] According to the present invention, the bulk density of the hydrogenation catalyst is 0.7-0.8 g / cm 3 .
[0061] According to the present invention, the specific surface area of the carrier is 250-500m 2 / g, preferably 280-400m 2 / g.
[0062] According to the present invention, the pore volume of the carrier is 0.6-0.8 mL / g, preferably 0.65-0.75 mL / g.
[0063] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the preparation method comprises the following steps:
[0064] (1) treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, an extrusion aid and a binder to obtain a carrier;
[0065] (2) mixing an aqueous solution containing an active component precursor and N-graphene to obtain an impregnation solution, wherein the active component precursor is selected from compounds of at least two of the metals M;
[0066] (3) impregnating the support into an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor;
[0067] or:
[0068] A. treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, N-graphene, an extrusion aid and a binder to obtain a base material;
[0069] B. mixing aqueous solutions containing active component precursors to obtain an impregnation solution, wherein the active component precursors are selected from compounds of at least two of the metals M;
[0070] C. Immersing the base material in an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor;
[0071] wherein the metal M is selected from Group VIII and Group VIB;
[0072] The amount of N-graphene used is such that the content of N-graphene in the prepared hydrogenation catalyst is 0.1-5wt% based on the total amount of the hydrogenation catalyst;
[0073] Wherein, the preparation method further comprises sulfiding the hydrogenation catalyst precursor to obtain the hydrogenation catalyst.
[0074] In the present invention, the preparation method can realize the preparation of the hydrogenation catalyst simply and efficiently, and the prepared hydrogenation catalyst has a large number of mesoporous structures and excellent hydrodesulfurization and denitrification performance.
[0075] In the present invention, the N-graphene is not particularly limited and can be prepared according to a common preparation method in the art or a commercial product.
[0076] According to the present invention, the aluminum-containing compound, the lanthanum-containing compound and the titanium-containing compound are used in such an amount that, based on the total amount of the hydrogenation catalyst, the content of lanthanum oxide is 1-10wt%, the content of titanium oxide is 1-10wt%, and the content of aluminum oxide is 40-77.9wt%.
[0077] In the present invention, the introduction of titanium oxide in the alumina-lanthanum oxide-titanium oxide composite carrier improves the hydrodesulfurization and denitrification performance of the hydrogenation catalyst. Specifically, titanium oxide has a variable valence state, which can adjust the surface properties of the carrier, change the distribution and chemical state of the active components, and enhance the hydrogen overflow activity.
[0078] According to the present invention, the amounts of the aluminum-containing compound, the lanthanum-containing compound and the titanium-containing compound are such that, based on the total amount of the hydrogenation catalyst, the content of lanthanum oxide in the prepared hydrogenation catalyst is 2-6wt%; the content of titanium oxide is 2-6wt%; and the content of aluminum oxide is 55-70.5wt%.
[0079] In the present invention, when the content of lanthanum oxide and titanium oxide is 2-6wt%, the hydrodesulfurization and denitrification performance of the hydrogenation catalyst is further improved.
[0080] According to the present invention, the amount of N-graphene used is such that the content of N-graphene in the prepared hydrogenation catalyst is 0.5-3 wt % based on the total amount of the hydrogenation catalyst.
[0081] According to the present invention, the active component precursor is used in an amount such that the content of the active component in the prepared hydrogenation catalyst is 20-35wt%, preferably 25-30wt%, based on the total amount of the hydrogenation catalyst.
[0082] According to the present invention, based on the total amount of materials fed in step (1) or step A, the amount of the extrusion aid is 1-5wt%, preferably 2-4wt%; the amount of the binder is 1-10wt%, preferably 4-8wt%.
[0083] In the present invention, the total amount of materials added in step (1) is the total amount of the aluminum-containing compound, the lanthanum-containing compound, the titanium-containing compound, the extrusion aid and the adhesive.
[0084] In the present invention, the total amount of materials fed in step A is the total amount of the aluminum-containing compound, the lanthanum-containing compound, the titanium-containing compound, N-graphene, the extrusion aid and the binder.
[0085] According to the present invention, in step (1) and step A, the treatment includes mixing, molding, drying and calcining.
[0086] In the present invention, the mixing and molding can be carried out using conventional equipment in the art, such as a kneader or an extruder.
[0087] According to the present invention, in step (1) and step A, the mixing conditions include: temperature of 20-30° C. and time of 0.5-1 h.
[0088] According to the present invention, in step (1) and step A, the drying conditions include: temperature of 90-120° C. and time of 1-4 h.
[0089] According to the present invention, in step (1) and step A, the calcination conditions include: temperature of 400-550° C. and time of 1-6 h.
[0090] In the present invention, the active component is loaded on the carrier by an equal volume impregnation method, and a suitable amount of active component precursor is added according to the water absorption rate of the carrier.
[0091] According to the present invention, in step (2), the mixing conditions include: temperature of 60-90° C. and time of 1-4 h.
[0092] According to the present invention, in step (3), the immersion conditions include: temperature of 20-60°C, preferably 25-40°C, and time of 0.5-5h, preferably 1-3h.
[0093] According to the present invention, in step (3), the calcination conditions include: a temperature of 400-550° C., preferably 400-500° C., and a time of 2-6 hours, preferably 3-5 hours.
[0094] According to the present invention, in step B, the mixing conditions include: temperature of 60-90° C. and time of 1-4 h.
[0095] According to the present invention, in step C, the immersion conditions include: temperature of 20-60°C, preferably 25-40°C, and time of 0.5-5h, preferably 1-3h.
[0096] According to the present invention, in step C, the calcination conditions include: a temperature of 400-550° C., preferably 400-500° C., and a time of 2-6 hours, preferably 3-5 hours.
[0097] According to the present invention, the extrusion aid is selected from at least one of starch, sesbania powder, polyvinyl alcohol, methyl cellulose and polyethylene glycol.
[0098] According to the present invention, the binder is selected from at least one of nitric acid, citric acid, oxalic acid and tartaric acid.
[0099] According to the present invention, the lanthanum-containing compound is selected from at least one of lanthanum-containing organic salts, lanthanum-containing inorganic salts and lanthanum-containing oxides, preferably at least one of lanthanum nitrate, lanthanum acetate, lanthanum oxide, lanthanum carbonate, lanthanum chloride and lanthanum acetylacetonate.
[0100] According to the present invention, the titanium-containing compound is selected from at least one of titanium-containing organic salts, titanium-containing inorganic salts and titanium-containing oxides, preferably at least one of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, titanium dioxide, titanium tetrachloride, titanium trichloride, titanium sulfate and metatitanic acid.
[0101] The aluminum-containing compound is selected from at least one of aluminum-containing organic salts, aluminum-containing inorganic salts and aluminum-containing oxides, and is preferably at least one of pseudo-boehmite, boehmite and gibbsite.
[0102] According to the present invention, the active component precursor is selected from at least two of a cobalt-containing metal compound, a nickel-containing metal compound, a molybdenum-containing metal compound or a tungsten-containing metal compound.
[0103] According to the present invention, the cobalt-containing metal compound is selected from at least one of cobalt oxide, cobalt hydroxide, cobalt nitrate, cobalt carbonate, basic cobalt carbonate, cobalt acetate and cobalt citrate.
[0104] According to the present invention, the nickel-containing metal compound is selected from at least one of nickel oxide, nickel hydroxide, nickel nitrate, nickel carbonate, basic nickel carbonate, nickel acetate and nickel citrate.
[0105] According to the present invention, the molybdenum-containing metal compound is selected from at least one of molybdenum trioxide, molybdic acid, ammonium molybdate, ammonium paramolybdate and phosphomolybdic acid.
[0106] According to the present invention, the tungsten-containing metal compound is selected from at least one of tungsten trioxide, tungstic acid, ammonium metatungstate hydrate, ammonium paratungstate and phosphotungstic acid.
[0107] In the present invention, the sulfurization in the preparation method can convert the metal M contained in the hydrogenation catalyst into a sulfide. The sulfurization can be conventional sulfurization in the art. The sulfurization can be directly carried out when preparing the hydrogenation catalyst, or the influence of oxidation of the catalyst during storage and transportation can be considered, and the online sulfurization can be carried out after the catalyst is filled before the formal hydrogenation reaction.
[0108] The third aspect of the present invention provides a hydrogenation catalyst prepared by the above preparation method.
[0109] A fourth aspect of the present invention provides use of the above hydrogenation catalyst in petroleum refining.
[0110] The present invention will be described in detail below through examples.
[0111] Unless otherwise specified, all reagents used in the present invention are commercially available.
[0112] N-Graphyne was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. The nitrogen content of N-Graphyne was greater than 10 wt% and not more than 20 wt%.
[0113] The surface morphology of the hydrogenation catalyst was characterized by transmission electron microscopy (TEM). The model of the TEM used was JEM-2010. The test conditions of the TEM were: operating voltage 200 kV.
[0114] The pore structure properties of the hydrogenation catalyst were detected by the BET test method. Specifically, ASAP2405M was used for the determination. The specific surface area and pore volume of the hydrogenation catalyst and the composite carrier were obtained by the Brunauer-Emmett-Taller (BET) method, and the mesopore distribution curve was calculated by the Barrett-Joyner-Halenda (BJH) method for the desorption curve.
[0115] The metal oxide content of the hydrogenation catalyst is obtained by calculation.
[0116] The lateral compression strength of the hydrogenation catalyst was measured by a particle strength testing machine, the instrument model was ZQJ-2.
[0117] Preparation Example - Preparation of composite carrier
[0118] Preparation Example 1
[0119] 100g of pseudo-boehmite, 11.9g of lanthanum nitrate hexahydrate (corresponding to 4.48g of lanthanum oxide), 19.04g of tetrabutyl titanate (corresponding to 4.48g of titanium oxide), 3.8g of sesbania powder, 3.8g of nitric acid and 3.8g of citric acid were weighed and added to deionized water, mixed evenly, kneaded, extruded into 1.5mm clover-shaped strips, dried at 100°C for 3h and then calcined at 500°C for 4h to obtain carrier A1. Based on the total amount of materials, the amount of the extrusion aid was 2.8wt%; the amount of the binder was 5.6wt%.
[0120] Preparation Example 2
[0121] 100g of pseudo-boehmite, 14.25g of lanthanum acetate (corresponding to 14.7g of lanthanum oxide), 42g of tetraethyl titanate (corresponding to 14.7g of titanium oxide), 5g of sesbania powder, 5g of nitric acid and 5g of citric acid were weighed, added to deionized water, mixed evenly, kneaded, extruded into 1.5mm clover-shaped strips, dried at 90°C for 2h, and then calcined at 500°C for 4h to obtain carrier A2. Based on the total amount of materials, the amount of the extrusion aid was 2.9wt%; the amount of the binder was 5.8wt%.
[0122] Preparation Example 3
[0123] 100g of pseudo-boehmite, 0.99g of lanthanum oxide, 0.99g of titanium oxide, 3.3g of sesbania powder, 3.3g of nitric acid and 3.3g of citric acid were weighed and added to deionized water, mixed evenly, kneaded, extruded into 1.5mm clover-shaped strips, dried at 120°C for 4h and then calcined at 500°C for 4h to obtain carrier A3. Based on the total amount of materials, the amount of the extrusion aid was 2.9wt%; the amount of the binder was 5.9wt%.
[0124] Preparation Example 4
[0125] 100g pseudo-boehmite, 6.3g lanthanum carbonate (corresponding to 4.48g lanthanum oxide), 10.64g titanium tetrachloride (corresponding to 4.48g titanium oxide), 2.24g N-graphene, 3.8g sesbania powder, 3.8g nitric acid and 3.8g citric acid were weighed, added to deionized water, mixed evenly, kneaded, extruded into 1.5mm clover-shaped strips, dried at 100°C for 3h, and then calcined at 500°C for 4h to obtain base material A4. Based on the total amount of materials, the amount of the extrusion aid was 2.9wt%; the amount of the binder was 5.8wt%.
[0126] Example - Preparation of Hydrogenation Catalyst
[0127] The amounts of the precursor and the carrier used in the examples are such that the contents of the components of the prepared hydrogenation catalyst are as shown in Table 1.
[0128] Example 1
[0129] The molybdenum oxide precursor and the nickel oxide precursor were dissolved in deionized water, heated to 70° C., N-graphene was added, and stirring was continued to mix evenly to obtain an impregnation solution B1.
[0130] The carrier A1 was added to the impregnation liquid B1, allowed to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C1. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0131] Example 2
[0132] The molybdenum oxide precursor and the cobalt oxide precursor were dissolved in deionized water, heated to 70° C., N-graphene was added, and stirring was continued to mix evenly to obtain an impregnation solution B2.
[0133] The carrier A1 was added to the impregnation solution B2, allowed to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C2. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0134] Example 3
[0135] The tungsten oxide precursor and the nickel oxide precursor were dissolved in deionized water, heated to 70° C., N-graphene was added, and stirring was continued to mix evenly to obtain an impregnation solution B3.
[0136] The carrier A1 was added to the impregnation solution B3, allowed to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C3. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0137] Example 4
[0138] The tungsten oxide precursor and the nickel oxide precursor are heated to 70° C. in deionized water, N-graphene is added, and the mixture is stirred and mixed to obtain an impregnation solution B4.
[0139] The carrier A2 was added to the impregnation solution B4, left to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C4. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0140] Example 5
[0141] The molybdenum oxide precursor, the nickel oxide precursor and the cobalt oxide precursor were dissolved in deionized water, heated to 70° C., N-graphene was added, and stirring was continued to mix uniformly to obtain an impregnation solution B5.
[0142] The carrier A3 was added to the impregnation liquid B5, allowed to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C5. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0143] Example 6
[0144] The molybdenum oxide precursor and the nickel oxide precursor were dissolved in deionized water, heated to 70° C., and mixed evenly to obtain an impregnation solution B6.
[0145] The base material A4 was added to the impregnation liquid B6, left to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst C6. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0146] Comparative Example 1-Conventional Hydrogenation Catalyst
[0147] Weigh 100 g of pseudo-boehmite, 3.8 g of sesbania powder, 3.8 g of nitric acid and 3.8 g of citric acid, add to deionized water, mix evenly, knead, extrude into 1.5 mm clover-shaped strips, dry and calcine at 500° C. for 4 h to obtain carrier DA1.
[0148] Ammonium molybdate and nickel nitrate were dissolved in deionized water, heated to 70° C., and mixed evenly to obtain an impregnation solution DB1.
[0149] The carrier DA1 was added to the impregnation liquid DB1, left to stand for 3 hours, dried at 110°C for 3 hours, and then calcined at 400°C for 5 hours to obtain the hydrogenation catalyst DC1. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0150] Comparative Example 2
[0151] A hydrogenation catalyst was prepared according to the preparation method of Example 1, except that the impregnation solution did not contain N-graphene. A hydrogenation catalyst DC2 was obtained. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0152] Comparative Example 3
[0153] A hydrogenation catalyst was prepared according to the preparation method of Example 1, except that the content of N-graphene was 6% based on the weight of the catalyst to obtain a hydrogenation catalyst DC3. The content of each component of the hydrogenation catalyst and the performance test are shown in Table 1.
[0154] Table 1*
[0155] C1 C2 C3 C4 C5 C6 DC1 DC2 DC3 <![CDATA[WO3,wt%]]> - - 23.5 23.5 - - - - NiO, wt% 4 - 4 4 2.5 4 4 4 4 CoO, wt% - 4 - - 1.5 - - - - <![CDATA[MoO3,wt%]]> 23.5 23.5 - - 23.5 23.5 23.5 23.5 23.5 <![CDATA[La2O3,wt%]]> 4 4 4 10 1 4 - 4 4 <![CDATA[TiO2,wt%]]> 4 4 4 10 1 4 - 4 4 N-Graphdyne, wt% 2 0.5 3 5 0.1 2 - - 6 <![CDATA[Specific surface area, m 2 / g]]> 230 235 245 240 230 230 270 220 210 Pore volume, mL / g 0.6 0.6 0.6 0.6 0.6 0.6 0.5 0.6 0.6 Lateral compressive strength, N / cm 170 170 180 170 173 170 175 168 170 <![CDATA[Bulk density, g / cm 3 > 0.80 0.80 0.80 0.80 0.80 0.80 0.82 0.80 0.80
[0156] *The remainder is alumina.
[0157] Test Case
[0158] Before use, the hydrogenation catalyst needs to be heated to the sulfurization temperature in a hydrogen atmosphere. After sulfurization, the evaluation raw material is switched and sampled for analysis after stabilization for 24 hours.
[0159] Test Case A
[0160] Using 8g of hydrogenation catalyst and coking diesel with a sulfur content of 7800ppm and a nitrogen content of 1300ppm as the evaluation raw material, a catalyst hydrogenation activity comparison test was carried out. The reaction conditions were a reaction temperature of 340°C, a hydrogen partial pressure of 6.4MPa, a hydrogen-to-oil volume ratio of 500:1, and a volume space velocity of 2.0h -1 The micro-reaction evaluation results of the hydrogenation catalyst are shown in Table 2.
[0161] Table 2
[0162] catalyst Desulfurization rate / % Denitrification rate / % C1 99.5 98.6 C2 99.2 93.3 C3 89.9 93.0 C4 89.5 91.5 C5 89.7 90.8 C6 90.0 92.3 DC1 86.0 83.0 DC2 88.9 90.0 DC3 89.0 90.1
[0163] Test Case B
[0164] Using 8g of hydrogenation catalyst, a comparative test of catalyst hydrogenation activity was carried out with aviation kerosene feedstock with a sulfur content of 6700ppm and a nitrogen content of 20ppm. The reaction conditions were a reaction temperature of 340°C, a hydrogen partial pressure of 7.0MPa, a hydrogen-to-oil volume ratio of 100:1, and a volume space velocity of 1.3h -1 The micro-reaction evaluation results of the hydrogenation catalyst are shown in Table 3.
[0165] Table 3
[0166]
[0167]
[0168] Test Case C
[0169] A hydrogenation activity comparison test was conducted using 8 g of hydrogenation catalyst and wax oil (distillation range 225-521°C) with a sulfur content of 900 ppm and a nitrogen content of 726 ppm as the evaluation raw material. The reaction conditions were a reaction temperature of 340°C, a hydrogen partial pressure of 12 MPa, a hydrogen-to-oil volume ratio of 800:1, and a volume space velocity of 1.5 h -1 The micro-reaction evaluation results of the catalyst are shown in Table 4.
[0170] Table 4
[0171] catalyst Desulfurization rate / % Denitrification rate / % C1 97.0 97.0 C2 96.3 96.0 C3 96.0 96.7 C4 95.5 95.9 C5 95.8 95.3 C6 95.0 96.5 DC1 90.0 86.5 DC2 94.5 94.6 DC3 95.0 95.1
[0172] It can be seen from the results in Tables 2-4 that Examples 1-6 using the hydrogenation catalyst of the present invention have more excellent hydrodesulfurization and denitrification performance.
[0173] Figure 1 This is the BET diagram of the hydrogenation catalyst of Example 1. It can be seen that the hydrogenation catalyst has a large number of mesoporous structures, and the pore diameters are concentrated around 10 nm, so that the hydrogenation catalyst provided by the present invention has excellent hydrodesulfurization and denitrification performance.
[0174] Figure 2This is a TEM image of the hydrogenation catalyst of Example 1. It can be seen that the catalyst forms an obvious layered stacking structure, so that the hydrogenation catalyst provided by the present invention has higher hydrodesulfurization and hydrodenitrogenation activity.
[0175] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrogenation catalyst, characterized in that The hydrogenation catalyst comprises: a carrier, an active component and N-graphene; wherein the active component is loaded on the carrier, and the N-graphene is loaded on the carrier or mixed in the carrier; Wherein, the carrier comprises an aluminum oxide-lanthanum oxide-titanium oxide composite carrier; Wherein, the active component is selected from sulfides of at least two kinds of metals M; Wherein, the metal M is selected from Group VIII and Group VIB; Wherein, based on the total mass of the hydrogenation catalyst, the content of N-graphene in the hydrogenation catalyst is 0.1-5wt%.
2. The hydrogenation catalyst according to claim 1, wherein Based on the total mass of the hydrogenation catalyst, the content of N-graphene in the hydrogenation catalyst is 0.5-3wt%; Preferably, based on the total mass of the hydrogenation catalyst, the content of lanthanum oxide in the hydrogenation catalyst is 1-10wt%, the content of titanium oxide is 1-10wt%, the content of aluminum oxide is 40-77.9wt%, and the content of active components is 20-35wt% in terms of oxides; Preferably, based on the total mass of the hydrogenation catalyst, the content of lanthanum oxide in the hydrogenation catalyst is 2-6wt%, the content of titanium oxide is 2-6wt%, the content of aluminum oxide is 55-70.5wt%, and the content of active components in terms of oxides is 25-30wt%.
3. The hydrogenation catalyst according to claim 1 or 2, wherein At least two of the metals M are selected from at least two of Mo, W, Co and Ni, preferably Mo-Ni, W-Ni, Mo-Co, Mo-Ni-Co, W-Ni-Co or W-Mo-Ni-Co.
4. The hydrogenation catalyst according to any one of claims 1 to 3, wherein The specific surface area of the hydrogenation catalyst is 200-300m 2 / g; Preferably, the pore volume of the hydrogenation catalyst is 0.4-0.7 mL / g; Preferably, the lateral pressure strength of the hydrogenation catalyst is 160-200 N / cm; Preferably, the bulk density of the hydrogenation catalyst is 0.6-0.9 g / cm 3 .
5. The hydrogenation catalyst according to any one of claims 1 to 4, wherein The specific surface area of the hydrogenation catalyst is 230-260m 2 / g; Preferably, the pore volume of the hydrogenation catalyst is 0.45-0.65 mL / g; Preferably, the lateral pressure strength of the hydrogenation catalyst is 170-190 N / cm; Preferably, the bulk density of the hydrogenation catalyst is 0.7-0.8 g / cm 3 .
6. A method for preparing a hydrogenation catalyst, characterized in that: The preparation method comprises the following steps: (1) treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, an extrusion aid and a binder to obtain a carrier; (2) mixing an aqueous solution containing an active component precursor and N-graphene to obtain an impregnation solution, wherein the active component precursor is selected from compounds of at least two of the metals M; (3) impregnating the support into an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor; or: A. treating an aluminum-containing compound, a lanthanum-containing compound, a titanium-containing compound, N-graphene, an extrusion aid and a binder to obtain a base material; B. mixing aqueous solutions containing active component precursors to obtain an impregnation solution, wherein the active component precursors are selected from compounds of at least two of the metals M; C. Immersing the base material in an impregnation solution, drying, and calcining to obtain a hydrogenation catalyst precursor; Wherein, the metal M is selected from Group VIII and Group VIB; The amount of N-graphene used is such that the content of N-graphene in the prepared hydrogenation catalyst is 0.1-5wt% based on the total amount of the hydrogenation catalyst; Wherein, the preparation method further comprises sulfiding the hydrogenation catalyst precursor to obtain the hydrogenation catalyst.
7. The preparation method according to claim 6, wherein: The aluminum-containing compound, the lanthanum-containing compound and the titanium-containing compound are used in such an amount that, based on the total amount of the hydrogenation catalyst, the content of lanthanum oxide is 1-10 wt %, the content of titanium oxide is 1-10 wt %, and the content of aluminum oxide is 40-77.9 wt %; Preferably, the aluminum-containing compound, the lanthanum-containing compound and the titanium-containing compound are used in such an amount that, based on the total amount of the hydrogenation catalyst, the content of lanthanum oxide is 2-6 wt %; the content of titanium oxide is 2-6 wt %; and the content of aluminum oxide is 55-70.5 wt %; Preferably, the amount of N-graphene used is such that the N-graphene content in the prepared hydrogenation catalyst is 0.5-3wt% based on the total amount of the hydrogenation catalyst; Preferably, the active component precursor is used in an amount such that the content of the active component in the prepared hydrogenation catalyst is 20-35wt%, preferably 25-30wt%, based on the total amount of the hydrogenation catalyst; Preferably, based on the total amount of materials fed in step (1) or step A, the amount of the extrusion aid is 1-5wt%, preferably 2-4wt%; the amount of the binder is 1-10wt%, preferably 4-8wt%.
8. The preparation method according to claim 6 or 7, wherein: In step (2), the mixing conditions include: temperature of 60-90° C. and time of 1-4 h; Preferably, in step (3), the conditions for the immersion include: a temperature of 20-60°C, preferably 25-40°C, and a time of 0.5-5h, preferably 1-3h; Preferably, in step (3), the calcination conditions include: a temperature of 400-550° C., preferably 400-500° C., and a time of 2-6 h, preferably 3-5 h; Preferably, in step B, the mixing conditions include: temperature of 60-90° C., time of 1-4 h; Preferably, in step C, the immersion conditions include: temperature of 20-60°C, preferably 25-40°C, time of 0.5-5h, preferably 1-3h; Preferably, in step C, the calcination conditions include: temperature of 400-550° C., preferably 400-500° C., and time of 2-6 h, preferably 3-5 h.
9. The preparation method according to claim 6 or 7, wherein: The lanthanum-containing compound is selected from at least one of a lanthanum-containing organic salt, a lanthanum-containing inorganic salt and a lanthanum-containing oxide, and is preferably at least one of lanthanum nitrate, lanthanum acetate, lanthanum oxide, lanthanum carbonate, lanthanum chloride and lanthanum acetylacetonate; Preferably, the titanium-containing compound is selected from at least one of titanium-containing organic salts, titanium-containing inorganic salts and titanium-containing oxides, preferably at least one of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, titanium dioxide, titanium tetrachloride, titanium trichloride, titanium sulfate and metatitanic acid; Preferably, the aluminum-containing compound is selected from at least one of an aluminum-containing organic salt, an aluminum-containing inorganic salt and an aluminum-containing oxide, and is preferably at least one of pseudo-boehmite, boehmite and gibbsite; Preferably, the active component precursor is selected from at least two of a cobalt-containing metal compound, a nickel-containing metal compound, a molybdenum-containing metal compound or a tungsten-containing metal compound; Preferably, the cobalt-containing metal compound is selected from at least one of cobalt oxide, cobalt hydroxide, cobalt nitrate, cobalt carbonate, basic cobalt carbonate, cobalt acetate and cobalt citrate; Preferably, the nickel-containing metal compound is selected from at least one of nickel oxide, nickel hydroxide, nickel nitrate, nickel carbonate, basic nickel carbonate, nickel acetate and nickel citrate; Preferably, the molybdenum-containing metal compound is selected from at least one of molybdenum trioxide, molybdic acid, ammonium molybdate, ammonium paramolybdate and phosphomolybdic acid; Preferably, the tungsten-containing metal compound is selected from at least one of tungsten trioxide, tungstic acid, ammonium metatungstate hydrate, ammonium paratungstate and phosphotungstic acid.
10. A hydrogenation catalyst prepared by the preparation method according to any one of claims 6 to 9.
11. Use of the hydrogenation catalyst according to any one of claims 1 to 5 and 10 in petroleum refining.
Citation Information
Patent Citations
Hydrofining method of low-grade gasoline / diesel oil
CN102851061A
Mesoporous magnesium oxide, hydrodesulfurization catalyst loading CoMo metal sulfide and application thereof
CN103157518A
Hydrofined catalyst and preparing process thereof
CN1052501A
Preparation method of hydrodesulfurization catalyst for high-nitrogen low-quality gasoline and diesel
CN102151582A
Hydro-fining catalyst roasted at low temperature and preparation method thereof
CN102784656A